Financial sector shocks, external finance premium and business cycle - Hongru Zhang (Cardiff University, Cardiff Business School, 2011)
This paper extends Nolan and Thoenissen (2009), hence NT, model with an explicit financial intermediary that transfer funds from households to entrepreneurs subject to a well defined loan production function. The loan productivity shock is treated as the supply side financial disturbance. Together with NT.s net worth shock that resembles the credit demand perturbation, both of the two-sided shocks are robustly extracted by combining the model with US quarterly data. The two shocks are found to be tightly linked with the post-war recessions. Each recession happens when both of the two shocks become contractionary. A few potential economic downturns seem to have been avoided because of the expansion of credit which offset the simultaneous contraction of entrepreneurial net wealth. This new introduced shock has significant explanatory power for the variance of EFP and the model simulated EFP holds high correlation with various spreads as proxies for empirical EFP.
Keywords: E32; E44; G21; 330; DSGE modeling; corporate net wealth shock; loan productivity shock; external financing; shock construction; historical decomposition; variance decomposition; Unternehmensfinanzierung; Industrieobligation; Schock; Konjunktur; Wirtschaftskrise; USA